Fear of Missing Out Scale Adaptation in Indonesia - Aurira, Puti; Andayani, Tri Rejeki; Supratiwi, Mahardika; Nursodiq, Fajar (UI Scholars Hub, 2023)
The study aimed to adapt the Fear of Missing Out (FoMO) Scale developed by Alt (2015). Instead of measuring FoMO only in a social context such as in previous studies, the development of this FoMO Scale was to also identify the levels of FoMO in the context of social media use during learning processes. The cross-cultural scale adaptation process referred to the forward-backward translation procedure by Beaton et al. (2000). Psychometric properties were assessed from its construct validation and reliability. Validation evaluation was carried out using Confirmatory Factor Analysis (CFA) from 534 samples of college students who experienced online lectures during the pandemic situation in Java. The construct validation supported the multidimensionality of the scale; Social FoMO, News FoMO, and Commercial FoMO had met the Goodness of Fit criteria (RMSEA ≤ 0,1; GFI ≥ 0,9; CFI≥ 0,8; AGFI ≥ 0,8) with factor loadings ranging from 0,42—0,74. The scale also proved to be reliable (ɑ=0,842). Thus, the Indonesian version of the FoMO Scale is eligible to measure the three dimensions of FoMO in Indonesia.